Gensko zdravljenje raka - Kočevar Britovšek, Nina (Farmacevtski vestnik, 2010)
Gene therapy uses genes to treat diseases. Large amount of research is based on cancer because current methods for cancer treatment have limited efficiencyand unwanted side effects. In the following article we first presentthe basic principles of gene therapy. Next, we describe the main delivery systems, which are viral and non-viral, and then the main therapeuticstrategies of cancer gene therapy. These can be divided into immunological, where we take advantage of the immune system for cancer cell killing through antigenic, stimulatory and costimulatory molecules, and molecular, where we take advantage of oncogene inactivation, tumor suppresor gene insertion, RNA interference, prodrug activating enzymes, oncolytic viruses, angiogenesis inhibition and insertion of drug resistance genes in hematopoietic progenitors
Keywords: gensko zdravljenje; nevirusni vektorji; rak (medicina); virusni vektorji